The Role of Pentacyclic Triterpenoids in Non-Small Cell Lung Cancer: The Mechanisms of Action and Therapeutic Potential - Young-Shin Lee; Ryuk Jun Kwon; Hye Sun Lee; Jae Heun Chung; Yun Seong Kim; Han-Sol Jeong; Su-Jung Park; Seung Yeon Lee; Taehwa Kim; Seong Hoon Yoon (Pharmaceutics)
Lung cancer remains a major global health problem because of its high cancer-related mortality rate despite advances in therapeutic approaches. Non-small cell lung cancer (NSCLC), a major subtype of lung cancer, is more amenable to surgical intervention in its early stages. However, the prognosis for advanced NSCLC remains poor, owing to limited treatment options. This underscores the growing need for novel therapeutic strategies to complement existing treatments and improve patient outcomes. In recent years, pentacyclic triterpenoids, a group of natural compounds, have emerged as promising candidates for cancer therapy due to their anticancer properties. Pentacyclic triterpenoids, such as lupeol, betulinic acid, betulin, oleanolic acid, ursolic acid, glycyrrhetinic acid, glycyrrhizin, and asiatic acid, have demonstrated the ability to inhibit cell proliferation and angiogenesis, induce apoptosis, suppress metastasis, and modulate inflammatory and immune pathways in NSCLC cell line models. These compounds exert their effects by modulating important signaling pathways such as NF-κB, PI3K/Akt, and MAPK. Furthermore, advances in drug delivery technologies such as nanocarriers and targeted delivery systems have improved the bioavailability and therapeutic efficacy of triterpenoids. However, despite promising preclinical data, rigorous clinical trials are needed to verify their safety and efficacy. This review explores the role of triterpenoids in NSCLC and therapeutic potential in preclinical models, focusing on their molecular mechanisms of action.